Quality evaluation of teaching and learning in higher education in Nigeria - Peingurta, Nifarta Adrew (Πανεπιστήμιο Πελοποννήσου, 2009)
lt has been argued that the ways students perceive and experience aspects of their courses and learning environment exerts a long pull on their satisfaction with their courses and the learning or skills that results, hence their evaluation of quality of their experiences. It follows therefore that, if students must get the best out of their courses, the quality of aspects of their courses and learning environment vίz-a-vίz the quality of teaching and learning must be evaluated regularly and consistently. Similarly, Ιf students are to appreciate the quality of education they receive, they must be allowed to evaluate the quality of their experiences since they are the active recipients of teaching and learning. Quality in higher education in Nigeria has been challenged both directly and indirectly by individuals and bodies that are concerned with the employment of graduates of higher institutions in the Nigerian labor market. It has also been purpeted that the quality of student's experiences of aspect of their courses and their learning environment is detororiating and is not the same all over the Nigerian Higher Institutions (Alonge, 2005). This research work therefore, focused mainly on carrying out an evidence research- based quality evaluation of teaching and learning via student's evaluation of the quality of aspects of theίr course experiences and learning environments in the Nigerian higher institutions, especially the university institutions; in order to substantiate and ascertain the above claims. Students evaluated the quality of their course experiences and learning environments based on a five point-scale measurement of the student's level of agreement with some statements concerning the quality of their course experiences and learning environment using the Student Course Experience Questionnaire (SCEQ) which we developed according to the style of questions found in Ramsden (1991). The instrument is made up of a total of 61 items spread over nine (sub-scales): Clear goals, Course level materials and facilities, good teaching, emphasis on independence, appropriate workload, appropriate assessment, surface learning strategy, deep learning strategy, generic skills and finally, overall satisfaction with course. The sub-scales were further categorized in to three major dimensions of intended curriculum, curriculum in action and learned curriculum. Α total of 2,221 students (response rate of 65.3%) evaluated the instrument from 17 universities selected at random all over the six geopolitical zones of Nigeria; comprising of both federal, state and private universities; representing 18.5% of total universities in Nigeria as at 2008.
Αριθμός Εισαγωγής: 009137
Keywords: Εκπαιδευτική αξιολόγηση; Εκπαίδευση, Ανώτατη -- Νιγηρία; Εκπαίδευση; Ποιότητα; Αξιολόγηση; Τριτοβάθμια εκπαίδευση; Νιγηρία